4(2r-3)-3(6r+1)=-25

Simple and best practice solution for 4(2r-3)-3(6r+1)=-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2r-3)-3(6r+1)=-25 equation:


Simplifying
4(2r + -3) + -3(6r + 1) = -25

Reorder the terms:
4(-3 + 2r) + -3(6r + 1) = -25
(-3 * 4 + 2r * 4) + -3(6r + 1) = -25
(-12 + 8r) + -3(6r + 1) = -25

Reorder the terms:
-12 + 8r + -3(1 + 6r) = -25
-12 + 8r + (1 * -3 + 6r * -3) = -25
-12 + 8r + (-3 + -18r) = -25

Reorder the terms:
-12 + -3 + 8r + -18r = -25

Combine like terms: -12 + -3 = -15
-15 + 8r + -18r = -25

Combine like terms: 8r + -18r = -10r
-15 + -10r = -25

Solving
-15 + -10r = -25

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -10r = -25 + 15

Combine like terms: -15 + 15 = 0
0 + -10r = -25 + 15
-10r = -25 + 15

Combine like terms: -25 + 15 = -10
-10r = -10

Divide each side by '-10'.
r = 1

Simplifying
r = 1

See similar equations:

| 3x+2=4x-[x-2] | | 6x+60=180 | | -7(-5x-10)=385 | | -2x+7=9 | | 11x-2=10x | | 2x+2x+30=3x+110 | | -(w+3)=-4x+10 | | 30x+9=11 | | 6x+60=90 | | (33.333)9cubed= | | 3b+16a-9n= | | -8x+5=-75 | | x^2-16x+89=0 | | 18x+7=29 | | (2w-3)(6-w)=0 | | (3x-5)=0 | | N+.5n=63 | | 0.7x+0.5=0.9x-0.7 | | 8(x+3)=4x+5 | | 3(y+7)=2(y+8) | | 6x+4=32 | | 2x-10-8=24-16-8x | | .143(49-7y)=14 | | -5(2-5x)+(-8x-2)=-4x-8x | | 6b=348 | | 15x/7=11/7 | | 3m-9x-1=24 | | 5-(.5)g=12 | | 5(4x-7)+13x-20=8(x+10)-15x+65 | | 15x/7=0 | | -[8z-(18z+3)]=3+(9z+10) | | 11x+2=10x+4 |

Equations solver categories